Pengaruh Capital Adequacy Ratio (CAR) Terhadap Profitabilitas Bank Umum Syariah di Indonesia Periode 2018-2024 - Cut Auliana Agma; Asyifa Zahra; Busra Busra (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the effect of the Capital Adequacy Ratio (CAR) on the profitability of Islamic Commercial Banks in Indonesia during the 2018–2024 period. Profitability is proxied by Return on Assets (ROA). The study employs a quantitative approach using secondary data obtained from the financial statements of Islamic Commercial Banks pub-lished by the Financial Services Authority and Bank Indonesia. The data were analyzed using simple linear regression, descriptive statistics, t-tests, and the coefficient of determination. The results indicate that CAR has a negative and signifi-cant effect on profitability, suggesting that high capital adequacy does not necessarily optimize profits because part of the capital has not been utilized productively. In the short term, excessive capital holdings may reduce profitability due to the existence of idle funds that are not allocated to productive financing activities. In the long term, effective capital manage-ment can improve operational efficiency, support sustainable financing expansion, strengthen financial stability, and ulti-mately enhance the profitability of Islamic Commercial Banks. This study provides empirical evidence regarding the rela-tionship between CAR and profitability in Islamic Commercial Banks during the most recent period up to 2024.